Karier Subkultural dan Kritisisme Street Artist Yogyakarta - Jagat Hidayat Jati; Derajad Widhyharto (Jurnal Studi Pemuda, 2020)
This article is based on research in 2017 about street artists in Yogyakarta. The study uses qualitative method with following issue and visuals approach on six street artists to extract 3 aspects: issue, medium, and actor.  Street artist as subcultural career is a process of creating space and efforts to maintain it. Street artists is mentally affected through perception of surroundings, then their awareness of reality and hopes for public spaces collide so that alternative spaces are created in the street walls, in the end the walls become space wich symbolically interpreted by the viewer. To be able to create space and maintain it, street artists have a side of criticism. Starting from the awareness of differences in public space, selection of street as a core element in the city, as well as accuracy in momentum. Criticism is carried out repeatedly and build a resistance identity. Each street artist is in a position to oppose and criticize the various problems that surround them through two work patterns, issue first or place first. The pattern is also carried out together to form a collective identity.